2020
DOI: 10.3390/ijerph17217939
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Health and Suspected Asthma among Hired Latinx Child Farmworkers in Rural North Carolina

Abstract: The aim of this study was to evaluate respiratory health problems, including suspected asthma, and healthcare provider utilization among a sample of Latinx hired child farmworkers in rural North Carolina (n = 140). In 2018, a respiratory health questionnaire and breathing tests were collected from Latinx child (11–19 years) farmworkers (35.0% girls and 65.0% boys). Overall, 21.4% of children reported having been told by a medical provider that they had asthma, yet based on a combination of responses to respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Musculoskeletal injuries are only one risk for these children. Other risks such as pesticide exposure, heat stress, and unintentional injuries incurred using equipment have both short and long term consequences 13,15,30–32 …”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal injuries are only one risk for these children. Other risks such as pesticide exposure, heat stress, and unintentional injuries incurred using equipment have both short and long term consequences 13,15,30–32 …”
Section: Discussionmentioning
confidence: 99%
“…This analysis uses interview data collected each year from 2017 through 2019 and pesticide exposure data collected with silicone wristbands in 2018 and 2019. The 2017 questionnaire addressed personal and work characteristics; results from this questionnaire have been published in several papers 41,55,60,62–64 . The questionnaires for 2018 and 2019 included items to measure current year work activities.…”
Section: Methodsmentioning
confidence: 99%
“…There are only a few studies evaluating the respiratory health of children working in agriculture; among them, a study in North Carolina found that 56.4% of the children had at least one respiratory problem [21]. Within the overall scope of the present study, analyses of adult workers indicate that 21.2% reported chest pain [12] and 7.4% reported cervical spine pain [11].…”
Section: Introductionmentioning
confidence: 65%
“…In general, it is done inside the barn so that workers are exposed to organic dust that increases the risk of respiratory problems [48]. A North American study [21] with children who worked in agriculture found that 16.4% had wheezing at some time in their lives, 14.3% had a persistent cough for more than ten days, and one-third had two or more respiratory problems. The prevalence of coughing without having a cold in the present study was higher than in the North American study [21] and, considering the difference in recall, 6.1% prevalence of wheezing in the last year was considerable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation